PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP OPTIMALISASI KUALITAS PELAYANAN ADMINISTRASI PADA KANTOR DESA WANUA WARU KECAMATAN MALLAWA KABUPATEN MAROS - Muhammad Erfan Mappincara; Muh Resky Iskandar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to determine the effect of competence and training on optimizing service quality at the Wanua Waru Village Office, Mallawa District, Maros Regency. The research used quantitative analysis. The data analysis method used was regression analysis, in this case multiple regression analysis using the SPSS version 26.0 application program. This analysis was used to examine factors influencing service quality. The results showed that competence (X1) had a partial positive and significant effect on service quality (Y). This means that increasing employee competence will tend to improve the quality of service provided. Competence explained 62.3% of the variation in service quality. Training (X2) also had a partial positive and significant effect on service quality (Y). This indicates that effective training can significantly contribute to improving service quality. Training can even explain 77.8% of the variation in service quality, making it a more dominant partial factor than competence.